2014
DOI: 10.1146/annurev-micro-091213-112844
|View full text |Cite
|
Sign up to set email alerts
|

The Medium Is the Message: Interspecies and Interkingdom Signaling by Peptidoglycan and Related Bacterial Glycans

Abstract: Peptidoglycan serves as a key structure of the bacterial cell by determining cell shape and providing resistance to internal turgor pressure. However, in addition to these essential and well-studied functions, bacterial signaling by peptidoglycan fragments, or muropeptides, has been demonstrated by recent work. Actively growing bacteria release muropeptides as a consequence of cell wall remodeling during elongation and division. Therefore, the presence of muropeptide synthesis is indicative of growth-promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 141 publications
2
59
0
1
Order By: Relevance
“…First, in all three co-cultures, changes were observed in the expression of genes involved in the biosynthesis or modification of peptidoglycan and lipopolysaccharides (Table 2, Figure 3). Peptidoglycan and lipopolysaccharides are components of the bacterial cell wall and outer membrane, and both have been suggested to mediate cell-cell recognition and signaling (Dworkin, 2014). Similar changes have been observed in different Synechococcus strains in response to co-culture (Tai et al, 2009;Beliaev et al, 2014).…”
Section: Resultsmentioning
confidence: 57%
“…First, in all three co-cultures, changes were observed in the expression of genes involved in the biosynthesis or modification of peptidoglycan and lipopolysaccharides (Table 2, Figure 3). Peptidoglycan and lipopolysaccharides are components of the bacterial cell wall and outer membrane, and both have been suggested to mediate cell-cell recognition and signaling (Dworkin, 2014). Similar changes have been observed in different Synechococcus strains in response to co-culture (Tai et al, 2009;Beliaev et al, 2014).…”
Section: Resultsmentioning
confidence: 57%
“…aureus STK1, may allow Inh2-B1 to attain a pose for a stronger and a stable interaction with the catalytic domain of STK1. A recent study has shown that the species-specific PASTA domain and associated free peptidoglycans somehow determine the specificity of the STK enzyme for its activation in response to external stimuli 64 . Our molecular docking analysis of Inh2-derivatives showing the highest affinity (−11.6 kCal/mol) of Inh2-B1 for the kinase domain of STK1 (PDB 4EQM) suggests that the tertiary structure (catalytic pocket) formed by the glycine-rich loop and the surrounding networks of amino acids contribute to the species-specific kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the presence of recycling pathways for muropeptides, the assembly and disassembly of cell wall does not represent a closed system, as some fragments of peptidoglycan escape into the environment. These fragments can induce inflammatory responses in hosts, provide protective immune modulatory signals, aid in initiating mutualism, and coordinate bacteria-bacteria interactions (reviewed in [6,7]).…”
Section: Introductionmentioning
confidence: 99%